Anthropometric Assessment of Nutritional Status of Children and Adolescents in Henanigala Indigenous Group, Sri Lanka - Ananda, T.; Nahallage, C. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2019)
The prevalence of undernourishment, is often higher among indigenous than non-indigenous children in many countries. However, lesser is known about the nutritional status of the Indigenous (the Veddas) children and adolescents in Sri Lanka. The present study was conducted to assess the nutritional status of the Henanigala Vedda children and adolescents through anthropometric measurements. Stature and weight of a total of 169 children and adolescents (90 girls and 79 boys between 5-18 years of age) were measured and calculated the Body Mass Index (BMI). Subjects were categorized into three age groups, 5-8 years (𝑛 = 28), 9-11 years (𝑛 = 52) and 12–18 years (𝑛 = 89). According to the National Health and Nutrition Examination Survey (NHANES) subjects who were falling below the age and sex specific fifth percentile (< 5th %ile) of the BMI Cut off Points were defined as undernourished. SPSS, MS Excel and BMI metric calculator for children, were used for data analysis. In order to test the level of significance, student t-test was performed (𝑃<0.05). Mean BMI of the girls of 5-8, 9-11 and 12-18 age categories were 13.22 ± 1.06, 13.39 ± 1.59 and 18.66 ± 3.42 respectively, boys were 14.78 ± 3.18, 14.76 ± 3.39 and 18.01 ± 3.38 respectively. The difference in stature was significant only between the boys and girls of the 12-18 age group. According to the BMI cut off points 67% of the girls and 60% of the boys of the 5-8 age group and 69% of the girls and 54% of the boys in the 9-11 age groups belonged to underweight category (critical). When compared with other age groups lower prevalence of underweight was found among 12-18 years age group which were 22% of girls and 35% of boys (but still at health risk). Higher prevalence of underweight among children could be due to the lower socioeconomic and educational status of their parents. In addition, sudden cultural transformations due to the resettlement which had an adverse effect on their traditional lifestyle including food practices would account for the lower nutritional status observed among the majority of the indigenous children and adolescents in Henanigala
Keywords: Anthropometrics, BMI, Vedda, Henanigala, Underweight